2017
DOI: 10.3928/23258160-20170601-05
|View full text |Cite|
|
Sign up to set email alerts
|

Retinal Ganglion Cell Loss in Children With Type 1 Diabetes Mellitus Without Diabetic Retinopathy

Abstract: There was a decreased GC-IPL thickness in children with T1DM without DR, suggesting that T1DM has an early neurodegenerative effect on retinal ganglion cells that occurs when the vascular component of DR is absent. SD-OCT may be more useful than ophthalmoscopic evaluation for detecting the earlier retinal structural changes of diabetes. [Ophthalmic Surg Lasers Imaging Retina. 2017;48:473-477.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
30
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 19 publications
6
30
0
3
Order By: Relevance
“…Changes in inner retinal structure before the development of DR Due to advancements in in vivo spectral-domain optical coherence tomography (SD-OCT) imaging of the retina (Jaffe & Caprioli, 2004), retinal layer thickness can be measured in vivo in diabetic humans and animal models at similar stages of diabetes as the retinal and visual activity measurements described above. In humans with diabetes but no DR, OCT measurements in vivo have shown smaller total retinal thickness (Bronson-Castain et al, 2012;Chen et al, 2016), retinal nerve fiber layer (RNFL) (Lopes de Faria et al, 2002;Verma et al, 2012;Gundogan et al, 2016), ganglion cell layer (GCL) (Van Dijk et al, 2010), and inner retina (Karti et al, 2017). Other studies have not found retinal thinning (Park et al, 2011;Dhamdhere et al, 2012), suggesting that this is something that develops over the course of diabetes (Pinilla et al, 2020).…”
Section: Changes In In Vivo Inner Retinal Activity Before the Developmentioning
confidence: 99%
“…Changes in inner retinal structure before the development of DR Due to advancements in in vivo spectral-domain optical coherence tomography (SD-OCT) imaging of the retina (Jaffe & Caprioli, 2004), retinal layer thickness can be measured in vivo in diabetic humans and animal models at similar stages of diabetes as the retinal and visual activity measurements described above. In humans with diabetes but no DR, OCT measurements in vivo have shown smaller total retinal thickness (Bronson-Castain et al, 2012;Chen et al, 2016), retinal nerve fiber layer (RNFL) (Lopes de Faria et al, 2002;Verma et al, 2012;Gundogan et al, 2016), ganglion cell layer (GCL) (Van Dijk et al, 2010), and inner retina (Karti et al, 2017). Other studies have not found retinal thinning (Park et al, 2011;Dhamdhere et al, 2012), suggesting that this is something that develops over the course of diabetes (Pinilla et al, 2020).…”
Section: Changes In In Vivo Inner Retinal Activity Before the Developmentioning
confidence: 99%
“…1 Microvascular complications can occur in young people with T1DM, [2][3][4] and diabetic retinopathy (DR) is considered to be the earliest and most common complication. 5,6 Optical coherence tomography (OCT) has shown reduced thickness of the retinal nerve fiber and ganglion cell layers in children with T1DM without retinopathy, which is suggestive of early neuronal damage. [6][7][8] Furthermore, in vivo corneal confocal microscopy (IVCCM), a rapid noninvasive ophthalmic imaging technique has also been shown to identify early corneal cellular and nerve fiber pathology in children and adolescents with T1DM, 9 adults with T1DM without neuropathy, 10 or retinopathy or microalbuminuria.…”
mentioning
confidence: 99%
“…5,6 Optical coherence tomography (OCT) has shown reduced thickness of the retinal nerve fiber and ganglion cell layers in children with T1DM without retinopathy, which is suggestive of early neuronal damage. [6][7][8] Furthermore, in vivo corneal confocal microscopy (IVCCM), a rapid noninvasive ophthalmic imaging technique has also been shown to identify early corneal cellular and nerve fiber pathology in children and adolescents with T1DM, 9 adults with T1DM without neuropathy, 10 or retinopathy or microalbuminuria. 11 Furthermore, reduced corneal nerve fiber length predicts the development of clinical diabetic neuropathy 12 and the development or worsening of retinopathy.…”
mentioning
confidence: 99%
“…Another recently published study confirmed these results, in part; however, it was assessing macular RNFL and GCL-IPL thickness in children with T1DM. Here, the GCL-IPL thickness was lower in all quadrants except the superior nasal quadrant in DM, while macular RNFL thickness showed no change [29].…”
Section: Studies Employing Sd-oct In Early Drmentioning
confidence: 75%